Visual Modeling and Analysis of EMF Model Transformations Based on Triple Graph Grammars - Ermel, Claudia; Hermann, Frank; Gall, Jürgen; Binanzer, Daniel (Electronic Communications of the EASST, 2012)
The tool HENSHIN is an Eclipse plug-in supporting visual modeling and execution of rule-based EMF model transformations. This paper describes the recent extensions of HENSHIN by a visual editor for triple graph grammars (TGGs). The visual editor (called HENSHINTGG) supports a compact visualization of triple rules in an integrated editor panel. Internally, triple graph rules are represented as HENSHIN rules and can be simulated using the HENSHIN EMF model transformation engine. Our extension supports the automatic generation of forward translation rules for transforming source into target models. A converter from HENSHIN TGG rules to the graph transformation analysis tool AGG allows a systematic check for conflicts of forward translation rules in AGG based on critical pair analysis.